2009
DOI: 10.1002/ijc.24154
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and sun protection: The impact of mixed public health messages in Australia

Abstract: Exposure of the skin to sunlight can cause skin cancer and is also necessary for cutaneous Vitamin D production. Media reports have highlighted the purported health benefits of Vitamin D. Our aim was to examine attitudes and behaviours related to sun protection and Vitamin D. A cross-sectional study of 2,001 residents in Queensland, Australia, aged 20-70 years was undertaken. Information collected included the following: skin cancer risk factors; perceptions about levels of sun exposure required to maintain Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
76
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 50 publications
11
76
3
Order By: Relevance
“…Due to the cross-sectional study design, we could not determine whether lack of knowledge about vitamin D resulted in reduced sun protection practices or whether people justified reduced sun protection behavior on the basis of perceived vitamin D requirements. However, these findings are consistent with the results of a recent survey in Queensland (11), suggesting that increasing knowledge may lead to improved sun protection practices.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Due to the cross-sectional study design, we could not determine whether lack of knowledge about vitamin D resulted in reduced sun protection practices or whether people justified reduced sun protection behavior on the basis of perceived vitamin D requirements. However, these findings are consistent with the results of a recent survey in Queensland (11), suggesting that increasing knowledge may lead to improved sun protection practices.…”
Section: Discussionsupporting
confidence: 89%
“…However, 11% of our sample believed that sun protection might lead to a lack of vitamin D. This is lower than the 32% reported by Youl and colleagues (11) and might be due to the difference in sampling frame. Nevertheless, as in the previous study, we also found that this attitude was more common among people with a lower frequency of sunscreen use.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…No less than 20 studies were recently published on this issue. These deal with items such as: the calculated UV exposure levels for a healthy vitamin D status (1); the high prevalence of vitamin D insufficiency (2); the vitamin D supplement doses and serum 25-hydroxyvitamin D in the range associated with cancer prevention (3); the knowledge and attitudes concerning vitamin D and impact of sun protection practices among urban office workers (4); the need for future sun protection campaigns to address the issue of vitamin D and present strategies to achieve sufficient vitamin D levels in countries with high UV radiation throughout the year (5); the attitudes, practices and knowledge of general practitioners with regard to vitamin D in relation to prescribing sunshine (6); the impact of public health messages in terms of vitamin D and sun protection, as well as protection against skin cancer (7); the hazard of UV radiation for children and adolescents (8); the evaluation, treatment and prevention of vitamin D deficiency considered in a clinical practice guideline (9); the effects of ambient sunlight and photoprotection on vitamin D status (10); the common genetic determinants of vitamin D insufficiency (11); an overview analysis of the time individuals spend outdoors (12); the effectiveness of casual exposure to summer sunlight for maintaining adequate vitamin D status (13); the possible reduction of vitamin D production to insufficient levels resulting from the widespread use of sun creams, particularly those with high sun protection factors (14); the optimal exposure to sunlight (16). In Germany, the matter under consideration was also far from being ignored.…”
Section: Introductionmentioning
confidence: 99%